Ethanolic extract of sappan wood (Caesalpinia sappan L.) inhibits MCF-7 and MCF-7/HER2 mammospheres' formation: an in vitro and bioinformatic study - Dhania Novitasari; Laeli Muntafiah; Nur Fitra Sari; Adam Hermawan; Edy Meiyanto (Indonesian Journal of Biotechnology, 2021)
One of the mechanisms of cancer cell resistance toward chemotherapy is through cancer stem cells (CSCs), which are characterized by excessive activation of regulator proteins such as human epidermal receptor 2 (HER2). Sappan wood (Caesalpinia sappan L.) contains brazilin and brazilein that exhibit cytotoxic effects on several cancer cell lines. We aimed to explore the potency of the ethanolic extract of sappan (EES) in CSCs through bioinformatic analyses and by using a three-dimensional (3D) breast cancer stem cells (BCSCs) for in vitro assay with two different models (i.e., BCSCs and HER2-BCSCs) in order to identify the potential therapeutic targets of genes (PTTGs). Bioinformatic analyses identiﬁed PTTGs, which were further analyzed by gene ontology, Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment, protein-protein interaction (PPI) networks, and hub protein selection. Mammospheres were cultured under conditioned media. The cytotoxic effects of EES were then measured by direct counting and based on the mammosphere-forming potential (MFP). Bioinformatic analysis disclosed PIK3CA and TP53 as PTTGs in BCSCs and HER2-BCSCs, respectively. In addition, the KEGG pathway analyses also demonstrated that PTTGs could regulate the ERBB pathway. EES thus demonstrated cytotoxicity and inhibited the formation of mammospheres. Collectively, EES exhibited excellent potential for further development as an inhibitor of cancer stem cells in breast cancer.